Peran Karotenoid Sebagai Pencegahan Degenerasi Makula - Aryani Vindhya Putri; Nabila Nurmalina; Alfa Sylvestris; Annisa Hanifwati (ARTERI : Jurnal Ilmu Kesehatan, 2022)
Macular degeneration or often called Age-related Macular Degeneration (AMD) is a degenerative disease that attacks the center of vision in the retina, namely the macula. In an effort to prevent the progression of AMD, consuming antioxidants has been shown to inhibit the AMD development process. Although currently there is no definite number of AMD sufferers in Indonesia, it is estimated that the number of AMD sufferers will continue to increase. Carotenoids are one of the antioxidant compounds that have been shown to inhibit the development of macular degeneration. Carotenoids are divided into several classes, one of which is the xanthophyll class. Lutein and zeaxanthin compounds belong to the xanthophyll class. The content of lutein and zeaxanthin in body plasma has been shown to reduce the risk of macular diseases such as AMD. This study aims to determine the role of carotenoids as the prevention of macular degeneration. The method used is a literature review in the form of a narrative review. Search literature in the form of journals and textbooks through Google Scholar, PubMed, Science Direct, and Research Gate, indexed by Scopus, ISSN, national journals and international journals. The journals used were published in the last 5 years and books published in the last 10 years. The results of the analysis show that carotenoid antioxidants are proven to be able to act as a prevention of AMD by reducing oxidative stress. Carotenoids will quench free radicals, thereby preventing the occurrence of lipid peroxidation, and preventing the formation of AMD. Carotenoids also prevent damage mediated by exposure to blue light. Consumption of lutein and zeaxanthin can also reduce the expression of VEGF (vascular endothelial growth factor) in the retina so that it can inhibit the increase of VEGF. It can be concluded that carotenoid antioxidants can prevent the progression of macular degeneration.